Vocal cues to eyewitness accuracy are detected by listeners with and without language comprehension - Philip Urban Gustafsson; Petri Laukka; Hillary Anger Elfenbein; Nutankumar S. Thingujam (Communications Psychology)
Abstract Criminal-law workers must evaluate the accuracy of eyewitness testimony, which includes nonverbal speech characteristics that may carry clues. Using a large collection of testimony statements (N = 3344), Study 1 showed that eyewitnesses use a higher speech rate, fewer pauses, and greater acoustic amplitude when remembering correctly and more confident in their answers. In Study 2, observers with vs. without language comprehension (Swedish vs. American and Indian samples) judged the accuracy of testimony statements and judged the eyewitness’ confidence. Participants performed at above-chance levels regardless of nation or language comprehension, suggesting universal cues to accuracy. Participants gave higher confidence ratings to correct statements, and this calibration was higher with greater cultural proximity to the testimony source. Observers’ confidence judgments were significantly correlated with amplitude, which suggests they used valid acoustical cues. Taken together, results demonstrate distinct vocal markers of eyewitness accuracy, which are detected by listeners from diverse cultures.